Statistical – Synoptic Analysis of the First Effective Precipitation in the Western and Northwestern of Iran - Mostafa Karimi; Ayob Jafari; Amir Bani Amerian; Seyfolah Kaki (جغرافیا و پایداری محیط)
One of the most important issues related to rainfed wheat cultivation is the date of the First Effective Precipitation (FEP) which can provide soil moisture for cultivation. The current study aims to evaluate the variability and probable trend in the date of the first effective precipitation and the synoptic conditions that lead to its occurrence in northwestern and western Iran. Therefore, precipitation data were extracted from Iran’s Meteorological Organization. First precipitation with a value of at least 5 mm and duration of one to two consecutive days, associated with another precipitation occurring less than 10 days apart, was selected as the first effective precipitation. Then, the trend of first effective precipitation was investigated using Man-Kendall test and linear regression method. Finally, geopotential height, wind speed and humidity data (ERA-Interim) at 850 and 500 hPa levels were obtained from ECMWF website to identify synoptic patterns of the first effective precipitation by cluster analysis method. The findings reveal that more than 90% of the first effective precipitation has occurred during October. Accordingly, Ardebil, Sanandaj, Khorramabad, Kermanshah, Zanjan, Orumieh, Tabriz and Hamadan stations had earliest climatic average of the first effective precipitation date during the period of 1987 to 2016, respectively. Despite the high annual variations regarding the occurrence date of first effective precipitation, evaluating the trend of the first effective precipitation by Mann-Kendall test at the significant level of 5% show that there is no significant trend in all studied stations. Furthermore, synoptic patterns including the short trough, omega block, cutoff low and the Mediterranean long trough are identified as responsible patterns on the occurrence date of the first effective precipitation. Among the patterns, omega block has been associated with widespread rainfall at the studied stations due to greater access to moisture and unstable conditions caused by the cold weather. Extended Abstract 1-Introduction Start date, especially for the first effective precipitation, is considered as one of the most important features of precipitation. Depending on its application, effective precipitation has different definitions in different sciences. In summary, the start date of the first effective precipitation is defined as the time when it reaches a total volume of 15 mm in the first month of the water year. Literatures review displayed that among different factors, the first effective precipitation has the most correlation with cultivation date especially for rainfed crops. Hence, the present study mainly aims to statistical-synoptic analysis of atmospheric patterns leading to the first effective rainfall under in west and northwest of Iran. 2-Materials and Methods Two types of data were used in order to fulfill the goal of research: a) precipitation data sets of the surveyed stations obtained from the Iranian Meteorological Organization during 1987-2016 statistical period. b) upper air data sets including geopotential height, specific humidity and zonal and meridional wind components obtained from the European Center for Medium- Range Weather Forecasts (ECMWF) at 850 and 500 hpa from 0 to 80º E longitude and 10 to 70º N latitude with a resolution of 2.5º×2.5º. Initially, First precipitation with a value of at least 5 mm and duration of one to two consecutive days, associated with another precipitation occurring less than 10 days apart, was considered as the First Effective Precipitation (FEP). Accordingly, the occurrence date of the first effective precipitation was specified and then converted to the Julian day (October 1st was taken as the first day of Julian calender). Then, the trend of changes in Julian day time series was investigated using trend analysis test including nonparametric Mann-Kendall test and linear regression method. Finally, based on climatic mean and Weibull distribution at the 75% probability level, the date occurrence of first effective precipitation was determined for each station. 3-Results and Discussion After determining the first 5 mm and more than 5 mm effective precipitation, the synoptic patterns of these precipitations were extracted at 500 hPa atmospheric levels. To do so, an 825×95 matrix (825 dots and 95 days) was formed. Then, correlation based cluster-hierarchical analysis was used to extract map patterns. At the final step, the extracted patterns were selected by post-processing and then a representative day was chosen from each pattern for drawing maps and interpreting the atmospheric circulation conditions. Of the 240 effective precipitation events during the 1987 to 2016 statistical period 166, 63 and 11 occurred in October, November, and December. Finally, respectively in all stations in question, 95 shared and non-shared days were specified from the total first effective precipitation in all stations. Most of the first effective precipitations were single-station. After that, most of the common days were observed in 2 and 3 stations with frequency of 16 and 15, respectively. Statistical analysis of the time trend of the first effective precipitation date showed that Tabriz, Sanandaj and Ardabil stations have had a positive trend. Accordingly, the first effective precipitation was associated with time delay and occurred later. On the other hand, Hamadan, Zanjan, Orumieh, Kermanshah and Khorramabad stations have shown negative trends, respectively. The negative gradient indicates a decreasing trend in the first precipitation date and the earliest effective rainfall was observed at these stations. Julian day trend by Mann-Kendall test at the significance level of 5% presented that the time variations in all stations were not significant at the 5% level. Moreover, annual variations in the first effective precipitation do not follow a specific pattern and the differences between each year have been reduced only within certain time intervals in each station. In general, all stations have been similar in terms of reducing differences in the date of the annual first effective precipitation. Furthermore, the least annual variations were observed in Ardabil, Sanandaj, Kermanshah, Khorramabad, Hamadan, Tabriz and Orumieh stations, respectively. Statistical analysis of the mean date at each station during the rainfall periods showed that the earliest start of precipitation occurred at Ardebil, Zanjan, Orumieh, Sanandaj, Khorramabad and Kermanshah stations, respectively. On the other hand, the latest precipitation was also related to Tabriz and Hamedan stations, respectively. Synoptic patterns including the short trough, omega block, cutoff low and the Mediterranean long trough were identified as responsible patterns on first effective precipitation date. The moisture source of all four patterns was the North Indian Ocean (Arabian and Red Seas) and the Mediterranean Sea, respectively. The results also represented that the identified patterns have the following characteristics: